2003
DOI: 10.1002/ejlt.200390019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2‐monoglycerides by alcoholysis of palm oil and tuna oil using immobilized lipases

Abstract: Synthesis of 2-monoglycerides by alcoholysis of palm oil and tuna oil using immobilized lipasesCommercial immobilized lipases were used for the synthesis of 2-monoglycerides (2-MG) by alcoholysis of palm and tuna oils with ethanol in organic solvents. Several parameters were studied, i.e., the type of immobilized lipases, water activity, type of solvents and temperatures. The optimum conditions for alcoholysis of tuna oil were at a water activity of 0.43 and a temperature of 60 °C in methyl-tert-butyl ether fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 16 publications
2
23
0
2
Order By: Relevance
“…Among them Lipase DF 15 exhibited a typo-selectivity leading to a strong discrimination against DHA while Lipase PS showed high deacylation activity without any selectivity. Similar discrimination against DHA has been already reported for alcoholysis with other enzymes (Wongsakul et al 2003;Halldorsson et al 2004). …”
Section: Resultssupporting
confidence: 66%
“…Among them Lipase DF 15 exhibited a typo-selectivity leading to a strong discrimination against DHA while Lipase PS showed high deacylation activity without any selectivity. Similar discrimination against DHA has been already reported for alcoholysis with other enzymes (Wongsakul et al 2003;Halldorsson et al 2004). …”
Section: Resultssupporting
confidence: 66%
“…Moreover, Moreno‐Perez et al described the synthesis of DHA TAGs catalyzed by different immobilized lipases achieving the best production yield with CAL‐B. Wongsakul et al found that CAL‐B discriminates DHA from EPA and can therefore be used for the selective enrichment of the more desirable DHA . Zhang et al investigated the production of TAGs enriched in EPA and DHA from fish oil using the same lipases than in the present work, and also described the same incorporation degree order of CAL‐B > TLL > RML.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that this lipase showed strict regiospecificity in the presence of excess ethanol. Wongsakul and coworkers [16] evaluated the synthesis of 2-MAG from palm and tuna oils by ethanolysis in organic solvents.…”
Section: Introductionmentioning
confidence: 99%